(untitled) (Revista de Medicina Clinica, 2018)
Introduction: Recent estimations calculate that there are 425 million people who suffer from diabetes and that 50% of them are unaware. In Mexico, about 4.5 million people are included within this percentage. Social constructs and professional biases are among the obstacles that hamper treatment initiation and long-term adherence to an insulin-based regimen. Objective: Compare the efficacy for insulin-based therapy in terms of its instalment, adherence, social beliefs and healthcare professional stances’ in Mexico and the other countries Background: Sociocultural factors associated with lack of adherence to insulin-based therapy, healthcare professionals’ stances towards this therapy and prejudices from patients with no prior insulin experience were analyzed and explained. Discussion: The actualization of background information on insulin-based treatments is proposed with the purpose of providing reliable information, solving patient doubts and allowing healthcare professionals to prescribe proper treatment schemes whilst creating a trusting environment and facilitating a consensus within the medical profession. Conclusion: Acquaintance with the current limitations allows healthcare professionals the ability to highlight areas of opportunity to evaluate solutions and improve the medical approach, resulting in greater efficacy in the treatment of the diabetic patient